Book review: Strengthening Postgraduate Supervision. McKenna, S., Clarence-Fincham, J., Boughey, C., Wels, H. and van den Heuvel, H. eds. 2017. - Paxton, Moragh (Critical Studies in Teaching and Learning, 2023)
Strengthening Postgraduate Supervision is a collection edited by Sioux McKenna, Jenny Clarence-Fincham, Chrissie Boughey, Harry Wels and Henk van den Heuvel. It emerged from the Strengthening Postgraduate Supervision (SPGS) Course which ran 45 times in 20 higher education institutions in South Africa. As the authors point out in the, preface, the book does not set out to provide a best practice guide to supervision but, rather, to present supervision as a complex and changing pedagogy which is fostered through experience and critical reflection.